Comparative analysis of metabolites in different Areca inflorescence tissues based on spatial metabolomics - Wen, Xinyu; Li, Panjing; Zhang, Linbi; Li, Han; Yang, Fusun (Frontiers in Plant Science, 2026)
In this study, we focused on the spatial distribution of metabolites in areca palm (Areca catechu L.) floral organs. Using spatial metabolomics, the composition and accumulation patterns of active metabolites were delineated to provide a basis for the development and utilization of their bioactive compounds. The present study combined untargeted metabolomics and mass spectrometry imaging, enabling high-resolution spatial visualization of metabolites in floral tissue microregions, with an emphasis on alkaloids, flavonoids, coumarins, and cinnamic acid. Significant differences in metabolite contents were observed using statistical methods and spatial metabolic mass spectrometry, revealing how these metabolites clustered and varied across tissues. Areca alkaloids exhibited specific enrichment in the ovary locules and ovule tissues of female flowers, showing concentrations 3–5 times higher than those in other tissues. Flavonoids were primarily localized in the vascular bundle sheath cells of the ovary wall. Although coumarins and cassia bark acids were distributed across all four tissue types, they displayed a gradient distribution pattern in the epidermal layer of female flower ovules. Using spatial metabolomics, this research reveals the compartmentalized distribution of metabolites across A. catechu floral organs, shedding light on their tissue-specific functions and related metabolic pathways.